PELATIHAN ADMINISTRASI PEMERINTAHAN KELURAHAN BERBASIS ONLINE DI KECAMATAN NAMBO KOTA KENDARI TAHUN 2022 - Sartono Sartono; La Ode Muhammad Elwan; Muhammad Yusuf; Taufik Taufik; La Ode Aslim (Universitas Halu Oleo, 2022)
Community service activities integrated with thematic Real Work Lectures (KKN) of Halu Oleo University aim to contribute to the government and citizens, especially in public services in the midst of the New Normal period in Southeast Sulawesi. This activity is an online-based Urban Village Administration Training in Nambo District, Kendari City, Southeast Sulawesi Province. The method used in the Thematic KKN is carried out directly at the activity location. Students are active from the beginning to the end of KKN activities carried out in the domicile area. The results of community service activities through Thematic KKN for students provide information that the average village government apparatus does not yet know and understand how to use internet technology facilities in public services, especially in managing village administration online based. There is only 1 website in the sub-district and all kelurahan do not yet have a website. There has never been any technical training on website management for village officials. Local government support is very limited in providing resources in realizing online-based urban administration.